Comparison of conventional and supercritical CO2 extraction techniques of Curcuma longa L. oleoresin and optimization of the spray drying process - BARRIGA-SÁNCHEZ, Maritza (2024)
Turmeric (Curcuma longa) is used as fresh turmeric and flour in Loreto, Peru. However, there are still no studies on the characterization and utilization of oleoresin as an input for the food industry. The objectives of this study were to compare conventional and supercritical CO2 extraction techniques of turmeric oleoresin and optimize the microencapsulation process through spray drying. Yield, curcuminoid content, total phenolic content (TPC), and antioxidant capacity (AC) of oleoresins obtained with supercritical CO2 and conventional extraction techniques were compared. Spray drying process parameters for microencapsulation of oleoresin were optimized. The highest extraction yield of oleoresin was obtained with ethanol and methanol. However, these extracts had low values of total curcuminoids of 25.81% and 29.31%, respectively. Oleoresins extracted with supercritical CO2 (SC-CO2), ethanol, and acetone showed high contents of TPC with 0.2697, 0.2602, and 0.2560 g GAE/g oleoresin, respectively, while oleoresin extracted with SC-CO2 had the highest AC by ABTS (2491.96 µmol TE/g oleoresin). Optimum conditions of spray drying were obtained with 190°C and a feed flow of 3.3 mL/min. In conclusion, Curcuma longa oleoresin is a valuable nutritional source for potential use in the food industry.